EVALUATION QUANTITATIVE DU SEL DES PRODUITS DE PANIFICATION POUR SA REDUCTION DANS LES PRODUITS ALIMENTAIRES - Alexandru Stoica; Mihaela F. Maria; Ana M. Hossu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Salt is a vital nutrient necessary for proper functioning of the body, but a large amount of salt is a risk factor in increasing blood pressure, the main cause of cardiovascular disease.The aim of this paper is to determine the percentage of salt in some bakery products in order to reduce the salt intake and to prevent the diseases caused by excessive consumption of salt. For bakery products, determination of sodium chloride was carried out according to Romanian Standard SR 91:2007. Argentometric titration method was used, by titration in the presence of potassium chromate (Mohr method).